2019
DOI: 10.1016/j.bone.2018.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic markers of an infradian biorhythm in human juvenile ribs

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Our previous studies suggest aspects of human growth may relate to RP-biorhythm. Specifically, we have shown that the size of microscopic canals that house blood vessels in human adolescent ribs relates to RP 49 . Larger canals facilitate greater blood flow and nutrient transfer 50 , 51 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our previous studies suggest aspects of human growth may relate to RP-biorhythm. Specifically, we have shown that the size of microscopic canals that house blood vessels in human adolescent ribs relates to RP 49 . Larger canals facilitate greater blood flow and nutrient transfer 50 , 51 .…”
Section: Introductionmentioning
confidence: 95%
“…Thus, in contrast to the interspecific positive correlation between the duration of growth periods and body size and RP, the idea is that stature and RP should correlate negatively in humans. Currently, however, evidence of the biorhythm in relation to human growth 49 , 52 is limited.…”
Section: Introductionmentioning
confidence: 99%